Color Atlas of Human Gross Pathology - Dawood, Gamal; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This pathology atlas includes information on all the body systems in one book with high quality photos of some of the rarest cases in pathology, e.g. dermatofibrosarcoma of toes, APKD in horseshoe kidney, extensive bilharzial polyposis of colon, and many other cases. The book is structured systematically to cover all body systems. Each system is organized to cover inflammatory and medical conditions, benign tumours, and ends with malignant tumours. Each photo is accompanied by a concise legend outlining the gross features important to notice during grossing. Emphasis is placed on how such patterns may aid in the correct diagnosis of the gross pathology. Gross pathology is an important part of studying pathology for medical and dental students. Any studied disease process must demonstrate the effects of this disease on the organ as observed by the naked-eye examination. So; this book will aid in the medical study of diseases. As for specialized surgical pathologists, the book will be a reference for them to describe or to aid in the diagnosis of some difficult cases, which may be faced during their work in the lab.
Cardiovascular System -- Respiratory System -- Gastrointestinal System -- Liver and Gall Bladder -- Urinary System -- Male Genital System -- Female Genital System -- Breast -- Lymphoreticular System -- Endocrine System -- Osseous System -- Skin and Soft Tissues -- Central Nervous System. .
Keywords: Pathology; Pathology; Disease; Pathology; Atlases